Applicability of Tableside Flat Panel Detector CT Parenchymal Cerebral Blood Volume Measurement in Neurovascular Interventions: Preliminary Clinical Experience - Mordasini, P. (AJNR Am J Neuroradiol, 2012)
BACKGROUND AND PURPOSE: CBV is a vital perfusion parameter in estimating the viability of brain parenchyma (eg, in cases of ischemic stroke or after interventional vessel occlusion). Recent technologic advances allow parenchymal CBV imaging tableside in the angiography suite just before, during, or after an interventional procedure. The aim of this work was to analyze our preliminary clinical experience with this new imaging tool in different neurovascular interventions. MATERIALS AND METHODS: FPD-CBV measurement was performed on a biplane FPD angiographic system. Eighteen patients (11 women, 7 men) were examined (age range, 18–86 years; median, 58.7 years). In the 10 patients with stroke, the extent of intracranial hypoperfusion was evaluated. The remaining 8 patients had an intracranial hemorrhage; periprocedural CBV was evaluated during the course of interventional treatment. RESULTS: In the 18 cases studied, 23 CBV measurements were performed. Twenty acquisitions were of sufficient diagnostic quality. The remaining 3 acquisitions failed technically, 1 due to motion artifacts and 2 due to injection technique and/or hardware failure. CONCLUSIONS: FPD-CBV measurement in the angiography suite provides a feasible and helpful tool for peri-interventional neuroimaging. It extends the intraprocedural imaging modalities to the level of tissue perfusion. However, the technique has technical limitations and shows room for improvement in the future.